Effects of Coenzyme Q10 on Statin‐Induced Myopathy: An Updated Meta‐Analysis of Randomized Controlled Trials. Issue 19 (2nd October 2018) - Qu, Hua; Guo, Ming; Chai, Hua; Wang, Wen‐ting; Gao, Zhu‐ye; Shi, Da‐zhuo
Abstract : Background: Previous studies have demonstrated a possible association between the induction of coenzyme Q10 (CoQ10) after statin treatment and statin‐induced myopathy. However, whether CoQ10 supplementation ameliorates statin‐induced myopathy remains unclear. Methods and Results: PubMed, EMBASE, and Cochrane Library were searched to identify randomized controlled trials investigating the effect of CoQ10 on statin‐induced myopathy. We calculated the pooled weighted mean difference (WMD) using a fixed‐effect model and a random‐effect model to assess the effects of CoQ10 supplementation on statin‐associated muscle symptoms and plasma creatine kinase. The methodological quality of the studies was determined, according to the Cochrane Handbook . Publication bias was evaluated by a funnel plot, Egger regression test, and the Begg‐Mazumdar correlation test. Twelve randomized controlled trials with a total of 575 patients were enrolled; of them, 294 patients were in the CoQ10 supplementation group and 281 were in the placebo group. Compared with placebo, CoQ10 supplementation ameliorated statin‐associated muscle symptoms, such as muscle pain (WMD, −1.60; 95% confidence interval [CI], −1.75 to −1.44; P <0.001), muscle weakness (WMD, −2.28; 95% CI, −2.79 to −1.77; P =0.006), muscle cramp (WMD, −1.78; 95% CI, −2.31 to −1.24; P <0.001), and muscle tiredness (WMD, −1.75; 95% CI, −2.31 to −1.19; P <0.001), whereas no reduction in the plasma creatine kinase level was observed after CoQ10 supplementation (WMD, 0.09; 95% CI, −0.06 to 0.24; P =0.23). Conclusions: CoQ10 supplementation ameliorated statin‐associated muscle symptoms, implying that CoQ10 supplementation may be a complementary approach to manage statin‐induced myopathy.